Comparison the degree of enamel wear behavior opposed to Polymer-infiltrated ceramic and feldspathic porcelain - Alireza Hashemi Ashtiani; Mohammad Azizian; Ali Rohani (Wolters Kluwer Medknow Publications, 2019)
Background: The degree of tooth enamel wear is an important aspect of the clinical acceptability of all-ceramic restorations. The purpose of this study was to compare the degree of enamel wear by feldspathic porcelain and polymer-infiltrated ceramic. Materials and Methods: In this in vitro study, 10 polymer-infiltrated ceramics were prepared by creating the sections of Vita Enamic® blocks (18 mm × 14 mm × 4 mm). A total of 10 porcelain cylinders were built, and feldspathic porcelain (VMK 95, Vita) was used and fired over the metal discs. A total of 20 human maxillary premolars were assigned as antagonist. Then, 10 teeth were arranged and placed oppose to porcelain samples and 10 others were placed oppose to polymer-infiltrated-ceramic specimens in the chewing simulator. The samples were photographed before and after the chewing simulation. The difference between the two photograph was measured by stereomicroscope and Motic Image plus software 2.0 three times, and then, the mean of these three times was recorded as the amount of wear. Data were analyzed using independent samples t-test and SPSS version 16. The level of significancy was 0.05. Results: The mean wear rate teeth oppose to the feldspathic porcelain group (377.294 μ) was significantly higher than that of the polymer-infiltrated ceramic group (101.755 μ) (P = 0.002). Conclusion: In the present study, the amount of enamel wear of the natural teeth opposed to polymer-infiltrated ceramic was significantly lower than feldspathic porcelain.